National Attitudes Toward Living Kidney Donation in the United States: Results of a Public Opinion Survey - Katya Kaplow; Jessica M. Ruck; Macey L. Levan; Alvin G. Thomas; Darren Stewart; Allan B. Massie; Hannah C. Sung; Sarah F. Pisano; Carolyn Sidoti; Dorry L. Segev; Joseph Sinacore; Amy D. Waterman (Kidney Medicine, 2024)
Rationale & Objective: Understanding national attitudes about living kidney donation will enable us to identify and address existing disincentives to living kidney donation. We performed a national survey to describe living kidney donation perceptions, perceived factors that affect the willingness to donate, and analyzed differences by demographic subgroups. Study Design: The survey items captured living kidney donation awareness, living kidney donation knowledge, willingness to donate, and barriers and facilitators to living kidney donation. Setting & Population: We surveyed 802 US adults (aged 25-65 years) in June 2021, randomly selected from an online platform with diverse representation. Analytical Approach: We developed summed, scaled indices to assess the association between the living kidney donation knowledge (9 items) and the willingness to donate (8 items) to self-reported demographic characteristics and other variables of interest using analysis of variance. All other associations for categorical questions were calculated using Pearson’s χ2 and Fisher exact tests. We inductively evaluated free-text responses to identify additional barriers and facilitators to living kidney donation. Results: Most (86.6%) of the respondents reported that they might or would definitely consider donating a kidney while they were still living. Barriers to living kidney donation included concerns about the risk of the surgery, paying for medical expenses, and potential health effects. Facilitators to living kidney donation included having information on the donation surgery’s safety, knowing that the donor would not have to pay for medical expenses related to the donation, and hearing living kidney donation success stories. Awareness of the ability to participate in kidney-paired donation was associated with a higher willingness to donate. Limitations: Potential for selection bias resulting from the use of survey panels and varied incentive amounts, and measurement error related to respondents’ attention level. Conclusions: Most people would consider becoming a living kidney donor. Increased rates of living kidney donation may be possible with investment in culturally competent educational interventions that address risks associated with donating, policies that reduce financial disincentives, and communication campaigns that raise awareness of kidney-paired donation and living kidney donation. Plain-Language Summary: Understanding what the general public thinks about living kidney donation will help to develop better education and increase the number of living kidney donors. We surveyed the public to find out: (1) how aware they are about the opportunity to donate a kidney while alive; (2) how much they know about living kidney donation; (3) whether they would be willing to donate; and (4) what would affect their willingness to donate. We found that teaching people about the risks of donating, decreasing costs related to donation, and raising awareness about it could increase the number of people willing to donate.